WALKABILITY DESIGN STUDY USING URBAN NETWORK ANALYSIS IN TANAH ABANG STATION AREA JAKARTA - Nourma Iksanti, Aline
In recent years, new urban design for walkability has become a major focus of city planning. Experts consider walking as one of the fastest and most reliable modes of short travel time, especially in the central area. Developments in transit areas have generally included walkability as a regional development concept where a walkable design encourages people to walk and switch from using motorized vehicles. The low number of Indonesians walking steps and the tendency to increase the use of motorized vehicles and inadequate pedestrian facilities have resulted in a lack of interest in walking. Walking is very compatible with the mixed use of land profile in Jakarta with compact blocks that can be easily accessed by pedestrians. This design study aims to improve regional walkability by comparing the existing Tanah Abang transit area and interventions based on Urban Network Analysis. UNA is a quantitative analysis tool that can be used to determine design interventions in walkability efficiency criteria of Tanah Abang transit area. Unlike previous network centrality tools that operate with two network elements, node and edge, the UNA tool includes a third network element, buildings that can be used as a spatial analysis unit. Tanah Abang Station area and settlement are separated by the west Ciliwung River and Jati Baru Bridge in east-west. The accessibility of pedestrian paths is a major problem for the region. The Tanah Abang Market as the largest economic generator in the area has experienced economic injustice due to the reduction in visitors to Block F since the opening of the skybridge connecting the Tanah Abang Station. The connection between Tanah Abang Market and settlements is only connected by two crossing bridges. The results of the UNA simulation are used as an analysis of problems in various elements of urban design such as land use, building mass intensity, parcel blocks, connectivity, placement of open space as a crowded and parking point so as to create a measurable design of the walkability efficiency criteria.